WALANT versus intravenous regional anesthesia for carpal tunnel syndrome: a randomized clinical trial - Okamura, Aldo; Moraes, Vinicius Ynoe de; Fernandes, Marcela; Raduan-Neto, Jorge; Belloti, João Carlos (São Paulo Medical Journal, 2021)
BACKGROUND: There are several anesthetic techniques for surgical treatment of carpal tunnel syndrome (CTS). Results from this surgery using the “wide awake local anesthesia no tourniquet” (WALANT) technique have been described. However, there is no conclusive evidence regarding the effectiveness of the WALANT technique, compared with the usual techniques. OBJECTIVE: To evaluate the effectiveness of the WALANT technique, compared with intravenous regional anesthesia (IVRA; Bier’s block), for surgical treatment of CTS. DESIGN AND SETTING: Randomized clinical trial, conducted at Hospital Alvorada Moema and the Discipline of Hand Surgery, Universidade Federal de São Paulo (UNIFESP), São Paulo (SP), Brazil. METHODS: Seventy-eight patients were included. The primary outcome was measurement of perioperative pain through a visual analogue scale (VAS). The secondary outcomes were the Boston Questionnaire score, Hospital Anxiety and Depression Scale (HADS) score, need for use of analgesics, operating room times, remission of paresthesia, failures and complications. RESULTS: The WALANT technique (n = 40) proved to be superior to IVRA (n = 38), especially for controlling intraoperative pain (0.11 versus 3.7 cm; P < 0.001) and postoperative pain (0.6 versus 3.9 cm; P < 0.001). Patients spent more time in the operating room in the IVRA group (59.5 versus 46 minutes; P < 0.01) and needed to use more analgesics (10.8 versus 5.7 dipyrone tablets; P = 0.02). Five IVRA procedures failed (5 versus 0; P = 0.06). CONCLUSIONS: The WALANT technique is more effective than IVRA for CTS surgery. TRIAL REGISTRY: NCT02986347. Clinical Question/ Level of Evidence: Therapeutic, II.